Density and magnetic fluctuations in type III-ELM pedestal evolution in JET: experimental and numerical characterization. (7th February 2018) - De Masi, G.; Predebon, I.; Spagnolo, S.; Meneses, L.; Delabie, E.; Lupelli, I.; Hillesheim, J. C.; Maggi, C.
Abstract: Density and magnetic fluctuation measurements in low- β type-III ELM discharges are obtained in the Joint European Torus (JET). They are observed during the inter-ELM pedestal evolution, after the LH transition phase, at about 60–70 kHz. Density fluctuations are measured with a correlation reflectometer system installed on the low-field side and they are localized at the pedestal top. Magnetic fluctuations with a spatial scale k y ρ i ∼ 0.1 are measured through a high resolution coil array. The main features and the relations with local plasma parameters are presented. The nature of these fluctuations is discussed along with linear gyrokinetic simulations. Ion temperature gradient (ITG) modes are the dominant instabilities in the frequency range of interest. In terms of radial localization, typical oscillation frequency and qualitative relation with the possible linear drive, ITG modes are consistent with the experimental density fluctuations measurements. Micro-tearing modes (MTMs), found unstable with a lower growth rate, appear a possible explanation for magnetic fluctuations in terms of typical wavenumbers and direction of propagation.